Analysis of ppkn teachers perceptions regarding the implications of nastionalist attitudes in efforts to preserve traditional dance - Maryani, Gina Yulia; Fitri Handayani, Nur; Pardosi, Jawatir; Bahzar, Moh (Universitas Tanjungpura, 2025)
This study aims to analyze the perceptions of civics teachers regarding the implications of nationalism in efforts to preserve traditional dance in schools. A qualitative approach was used with data collection techniques through in-depth interviews with civics teachers in several schools in Samarinda City. The results of the study show that teachers interpret nationalism not only as a sense of love for the homeland, but also as concrete actions that reflect concern for local culture, such as through participation in traditional dance activities. Teachers consider the preservation of traditional dance to be an effective means of instilling national values in students, especially when it is contextually linked to everyday life. However, a major challenge comes from the dominance of foreign popular culture, which is more appealing to students, as well as the lack of structural support in the form of policies or incentives from schools and the government. Teachers implement various innovative strategies, such as project-based learning, the use of digital media, and direct involvement in traditional dance preservation activities, to maintain the sustainability of nationalism amid globalization. This study recommends the need for synergy between schools, families, and the government in strengthening character education so that the younger generation does not become alienated from their cultural identity. The preservation of traditional dance in schools, if supported systematically, can be a strategic vehicle for strengthening the character and identity of the nation